Semi-universal deformation spaces of some simple elliptic singularities - Nakamoto, Kazunori; Tosun, Meral (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2007)
In this Note, we deal with the simple elliptic singularities of type (D) over tilde (5). By using the Lie algebra sl(2,C) circle plus sl(2,C), we construct semi-universal deformation spaces of these singularities.
Keywords: Mathematics